Implementation of the Failure Mode and Effects Analysis (FMEA) Method to Determine Project Risk Priority. Issue 1 (July 2020) - Atin, S; Lubis, R
Abstract: The purpose of this research is to determine the priorities of risks that might occur so that the implementation of project work can run smoothly and later can be used as a basis for making decisions in handling the project being worked on. One method that can be used to determine the priority of risks that arise in a project is the Failure Mode and Effects Analysis (FMEA). FMEA is one of the methods used to prevent project failures caused by project risks that arise. The results of this study are FMEA can be used to handle and determine the priority of risks that arise in the project and can be used by the person in charge of the project in making decisions in handling risks that arise in the project. By using FMEA project risks can be prevented and completed so that the project can be completed on time.